INDEKS KEPUASAN MASYARAKAT ELECTRONIC SERVICE QUALITY PADA APLIKASI LAPAK PROBOLINGGO DI KANTOR KELURAHAN SIDOMUKTI KECAMATAN KRAKSAAN - Siti Marwiyah; Verto Septiandika; Murtias Puji Astutik (Jurnal Ilmiah Hospitality, 2022)
This study aims to determine internet-based services at the Sidomukti Village Office, Kraksaan District, Probolinggo Regency as measured using the Community Satisfaction Index. Data collection techniques were carried out by means of observation, questionnaires, interviews and documentation. The data analysis method uses simple regression analysis using quantitative descriptive research methods with a phenomenological approach. From the results of the study, it can be seen that the Community Satisfaction Index (IKM) for services at the Sidomukti Sub-District Office, Kraksaan District is 2.91 with a conversion rate of 72.75 which can be declared "Not Good". This is because the community is still not satisfied with the performance of the Probolinggo application service unit at the Sidomukti Village Office, Kraksaan District, Probolinggo Regency. For this reason, it is necessary to make improvements to several elements that are still considered lacking. The indicator that has the highest IKM value is Usability with an IKM value of 5.89 with an IKM conversion value of 73,625. While the indicator that has the lowest IKM value is the Graphic Style indicator, which gets an IKM value of 2.66 and an IKM conversion value of 33.25